2002
DOI: 10.1128/mcb.22.1.332-342.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role for the Related Poly(ADP-Ribose) Polymerases Tankyrase 1 and 2 at Human Telomeres

Abstract: Telomere maintenance is essential for the continuous growth of tumor cells. In most human tumors telomeres are maintained by telomerase, a specialized reverse transcriptase. Tankyrase 1, a human telomeric poly(ADP-ribose) polymerase (PARP), positively regulates telomere length through its interaction with TRF1, a telomeric DNA-binding protein. Tankyrase 1 ADP-ribosylates TRF1, inhibiting its binding to telomeric DNA. Overexpression of tankyrase 1 in the nucleus promotes telomere elongation, suggesting that tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
296
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(312 citation statements)
references
References 40 publications
13
296
1
2
Order By: Relevance
“…In conclusion, the present study has identified PARP-2 as an additional contributor to telomere functions by regulating TRF2, whereas tankyrase 1 and 2 have been shown to target TRF1 (15). The identification of several PARP homologues regulating telomere protection and/or synthesis adds to the complexity but undoubtedly reinforces the increasing number of molecular processes needed for functional telomeres (7).…”
Section: Discussionmentioning
confidence: 94%
“…In conclusion, the present study has identified PARP-2 as an additional contributor to telomere functions by regulating TRF2, whereas tankyrase 1 and 2 have been shown to target TRF1 (15). The identification of several PARP homologues regulating telomere protection and/or synthesis adds to the complexity but undoubtedly reinforces the increasing number of molecular processes needed for functional telomeres (7).…”
Section: Discussionmentioning
confidence: 94%
“…TANK-mediated ADP-ribosylation causes TRF1 to dissociate from telomeric DNA in vitro [68]. Moreover, when nuclear-targeted TANK1 is overexpressed in telomerase-positive human cells, telomeres elongate, consistent with TANKs inactivating TRF1 in vivo and TRF1 being a negative regulator of telomere length [70,74].…”
Section: Telomere-associated Proteins With Non-telomeric Functionsmentioning
confidence: 87%
“…3). Although the TANKs can be found at telomeres, and even ADP-ribosylate TRF1 in vitro [68,70], these proteins reside predominantly in Golgi-type vesicles, and have also been identified at centrosomes [69,[71][72][73]. The precise functions of TANKs are not known.…”
Section: Telomere-associated Proteins With Non-telomeric Functionsmentioning
confidence: 99%
“…Several of the PARP family proteins may be associated with telomeres. Tankyrases 1 and 2, as well as PARP1 and 2, can directly bind to and poly-ADP ribosylate the telomeric repeat binding factors 1 (TRF1) and 2 (TRF2) and affect their association to telomeric DNA, acting as positive regulators for telomere elongation (Smith and de Lange, 1999;Kaminker et al, 2001;Cook et al, 2002;Rippmann et al, 2002). In addition, upon DNA damage, PARP1 may be recruited to the damaged telomeres, helping to protect telomeres against chromosome end-to-end fusions and genomic instability (Gomez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%